Safeguarding young people beyond the family home responding to extra-familial risks and harms. (POLICY PRESS, 2022)
During adolescence, young people are exposed to a range of harms and risks beyond their family homes and this book assesses social care organisations' safeguarding responses across 10 countries. The authors highlight key areas for service development and give insights into how these risks and harms can be responded to in the future.